Heroicity and identity in the Hellenistic novel Quéreas and Calírroe - Álvarez Espinoza, Nazira (2020)
In the social and cultural context of the Hellenistic world a new heroic model surface. The fictional representation modifies the traditional role models of femininity and mas- culinity. The changes may be observed in the novel of Chariton of Aphrodisias Chaereas and Callirhoe, considered the oldest text of the genre novel. The representation of the protagonists tests the dichotomy of the traditional spaces assigned for men and women. Hence the geographic and social spaces and the material and symbolic limitations, and the differences in gender hierarchies are subverted and interchanged temporarily by Chaereas and Callirhoe in order to overcome the obstacles of their adventure. The analy- sis is made from a spatial perspective associated with the concepts of space, identity, frontiers, limits, borders, citizenship, xenia, exile and liminality.